Perakitan Padi Lokal Semidwarf Berbasis Genome Editing dengan Target Mutagenesis Gen Pengkode GA20ox2 (SD-1) yang Dimediasi Agrobacterium tumefaciens Strain LBA4404 - Hilda Ramadhani (Fakultas Pertanian, 2026)
Semidwarf1 (SD1) is a gene encoding the enzyme Gibberellin-20-Oxidase-2 (GA20ox2), which plays a role in gibberellin biosynthesis, which regulates rice plant height. The SD1 gene was first discovered in the Dee-Geo-Woo-Gen (DGWG) variety, which naturally experienced a semidwarf allele mutation in the form of a 383-bp sequence deletion. Mutations in the SD1 gene cause plant stems to become semidwarf due to the inhibition of gibberellin biosynthesis, resulting in decreased GA1 production. The SD1 gene produces a stem morphology with a height of around 90-110 cm so that the plant becomes more resistant to lodging and is able to adapt to high nitrogen fertilization. This study used a genome editing method on the SD1 gene with the pRGEB32 plasmid mediated by Agrobacterium tumefaciens to regulate the height pruning of rice plants through the SD1 gene knockout process. This study aims to reveal the impact of the SD1 gene knockout on the gibberellin biosynthesis pathway in rice plants through a genetic transformation process. This study was conducted at the Agrotechnology Laboratory, Faculty of Agriculture, University of Jember. The results of the study were analyzed using simple descriptive statistics to obtain an overview of the efficiency of gene transformation into the plant genome. The results of this study were obtained confirmation of the transformation of the pRGEB32::SD1 plasmid into Agrobacterium tumefaciens through PCR analysis with HPTII markers, the success of the transformation of Agrobacterium tumefaciens inserted with the pRGEB32::SD1 plasmid into rice callus varieties Siam Epang, Mentik Susu, and Koshihikari was indicated by the presence of putative transformant plants. And the results of confirmation of transformant rice plants that have been transformed by T-DNA into the plant genome through PCR analysis with HPTII markers and pRGEB32::SD1.sgRNA1 as positive transformant plants were obtained.
FINALISASI oleh Arif 2026 Mei 26
Keywords: Genome Editing; Semidwarf1; Rice Plant